2020
DOI: 10.26686/wgtn.12331253.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How LGBT+ Young People Use the Internet in Relation to Their Mental Health and Envisage the Use of e-Therapy: Exploratory Study

Abstract: BACKGROUND: Lesbian, gay, bisexual, and transgender (LGBT) youth and other young people diverse in terms of their sexuality and gender (LGBT+) are at an elevated risk of mental health problems such as depression. Factors such as isolation and stigma mean that accessing mental health services can be particularly challenging for LGBT+ young people, and previous studies have highlighted that many prefer to access psychological support on the Web. Research from New Zealand has demonstrated promising effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…These conversations put further emphasis on the need for the development of mental health e-therapies tailored for LGBTQI+ users. Lucassen et al (2018) state that LGBTQI+ youths were interested in eHealth tools (as shown in their study on the Rainbow SPARX program), reporting positive responses. Due to the complexities of language that was deemed patronizing of certain phrases utilized in the program, future e-health or mhealth developments could include preference levers where individuals can personalize the customization of e-therapy profiles, aiding their utility for long-term mental health improvements.…”
Section: Lgbtqi+mentioning
confidence: 99%
“…These conversations put further emphasis on the need for the development of mental health e-therapies tailored for LGBTQI+ users. Lucassen et al (2018) state that LGBTQI+ youths were interested in eHealth tools (as shown in their study on the Rainbow SPARX program), reporting positive responses. Due to the complexities of language that was deemed patronizing of certain phrases utilized in the program, future e-health or mhealth developments could include preference levers where individuals can personalize the customization of e-therapy profiles, aiding their utility for long-term mental health improvements.…”
Section: Lgbtqi+mentioning
confidence: 99%